Sistem Pendukung Keputusan Pemilihan Instruktur Komputer Terbaik Menerapkan Metode Profile Matching - Nurmayana Sari; Mesran; Fadlina (Bulletin of Computer Science Research, 2023)
The development of computer technology is now very rapid and familiar, making us have to learn how to use computers to increase our knowledge and skills so that they can help and facilitate our daily activities. LKP IBAY COMPUTER is a Course and Training Institute especially in the field of computer technology. The learning process is guided by experienced instructors who are also experts in their fields. Decision support systems are systems used in making decisions based on existing criteria. To help and facilitate agencies in choosing the best computer instructor, a decision support system is created that is able to provide alternative solutions. In this study the method used is the Profile Matching method. The calculation process in the Profile Matching method is by defining the minimum value for each assessment variable. The difference between each testing data value to the minimum value of each variable is a gap which is then given a weight, the smaller the resulting gap, the greater the weight of the value, so that there is a greater chance for someone to be selected as the best instructor. The Profile Matching method is used to provide an assessment of the best alternative considerations from the various options available. Processing values ??using the profile matching method will produce rankings.